Empresas portuguesas e a sua internacionalização: estudo do caso – a empresa Corticeira Amorim, SGPS - Santos, Maria Manuela da Silva (2022)
Market globalization, along with other variables such as technological growth allows the markets to be in constant dynamism. Portuguese companies had to adapt to a new reality. This propelled internationalization and competition between all businesses. New challenges and new trade expansion opportunities emerged. Internationalization is a crucial bussiness strategy to guarantee a company´s sustainability and, at the same time, to optimize economical growth. The main goal of this dissertation is to study, describe, analyze, synthesize, evaluate and interpret from the case study, the process of internationalization of Corticeira Amorim, as well as analzye the repercussions of COVID-19 in the companies. The methods chosen for this monographic dissertation, were from an exploratory case study, following a qualitative approach, a gathering, evaluation and analysis of the secondary and primary data was made. Books, scientific articles, statement of accounts, doctoral theses, master’s dissertations, projects, semi-structured interview and Websites. It was concluded that Corticeira Amorim showed signs of utilizing the Uppsala model, so this was a gradual learning process where Joint-ventures were used as a way to enter the external market. Despite the global pandemic and all of its lockdown restrictions, the company continued their economic activity with all the safety and guidelines of the World Health Organization, in order to continue to serve their clients. In 2019 and 2020 there was a decrease in the business volume, however the net results were always positive. In 2021, the business volume reached higher values to those before the pandemic. Currently the company is in a stage of strong economic growth.